2012
DOI: 10.1016/s1995-7645(12)60033-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of soy isoflavone supplements on osteoporosis in women

Abstract: The present meta-analysis reveals that soy isoflavone supplements significantly increase bone mineral density and decrease the bone resorption marker urinary DPD. It shows no significant effect on bone formation markers serum bone alkaline phosphatase. The significant effect of soy isoflavones on BMD and urinary DPD is relative to menopausal status, supplement type, isoflavone dose and intervention duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
1
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 28 publications
0
80
1
15
Order By: Relevance
“…A previous study indicated that estrogen use increases the performance on certain tests of cognition, particularly in postmenopausal women (20). Short-term high-dose soy bean intake altered the levels of total plasma testosterone and improved spatial cognition in women (24).…”
Section: Effects Of Soy Isoflavones On Learning and Memorymentioning
confidence: 94%
See 2 more Smart Citations
“…A previous study indicated that estrogen use increases the performance on certain tests of cognition, particularly in postmenopausal women (20). Short-term high-dose soy bean intake altered the levels of total plasma testosterone and improved spatial cognition in women (24).…”
Section: Effects Of Soy Isoflavones On Learning and Memorymentioning
confidence: 94%
“…Natural or surgical menopause results in an initial phase of rapid bone loss followed by a period of slower skeletal deterioration (19). This rapid phase of bone loss occurs within the first 10 years following the cessation of menses or surgical removal of the ovaries (20). The ovarian hormone deficiency associated with menopause results in an increased rate of bone turnover and leads to an imbalance between resorption and formation, thereby accelerating bone loss (21).…”
Section: Osteoporosis and Soy Isoflavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que a perda de massa óssea está relacionada com a idade e é maior em mulheres do que em homens. A deficiência hormonal quando associada com os efeitos da menopausa, causa um aumento da taxa de remodelação óssea, provocando um desequilíbrio entre a reabsorção e formação, o que acelera a perda óssea [19,32].…”
Section: Benefícios Do Consumo De Produtos à Base De Sojaunclassified
“…A relação entre as isoflavonas de soja e o tecido ósseo tem sido estudada há pouco menos de dez anos, dados obtidos através de diversos estudos com animais demonstraram que as isoflavonas de soja possuem efeitos de conservação óssea na retenção de massa óssea após ovariectomia [32]. O possível papel desempenhado pelas isoflavonas de soja na modificação de massa óssea humana é de que os suplementos de proteína de soja enriquecidos com isoflavonas atenuam a perda óssea na pós-menopausa e também na pré-menopausa em mulheres.…”
Section: Benefícios Do Consumo De Produtos à Base De Sojaunclassified